Analisis Semiotika Roland Barthes pada Film Warkop DKI: Dongkrak Antik–Scene Paman Mat Solar Ngamuk - Muhammad Lutfan Alfarizki; Radea Yuli A Hambali (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to determine the signs and meanings contained in a film based on Roland Barthes semiotic analysis. This type of research is qualitative research and the method used in this research is descriptive analysis study. This research shows that there are three signs and meanings contained in the three scenes, where each scene has a different meaning and is full of cultural values and conditions of public service in Indonesia. The meaning of the first sign is about the crisis of creativity in Indonesian society, where this occurs quite comprehensively in the life of contemporary society. The meaning of the second sign is the apathy of the people who are indifferent to the surrounding environment. The meaning of the third sign is the badness of government agencies in providing social services to Indonesian people, such as public health agencies or hospitals. This study concludes that there is a meaning that is full of the social conditions of society and government services to the people of Indonesia. Researchers hope that there will be more research on a film that describes the social conditions of society using the analytical knife of Roland Barthes or other semioticians.